National Athletic Trainers' Association position statement: Prevention of pediatric overuse injuries - Valovich McLeod, T. C.; Decoster, L. C.; Loud, K. J.; Micheli, L. J.; Parker, J. T.; Sandrey, M. A.; White, C. (Journal of Athletic Training, 2011)
Objective: To provide certified athletic trainers, physicians, and other health care professionals with recommendations on best practices for the prevention of overuse sports injuries in pediatric athletes (aged 6-18 years).